High-Performance Perovskite Solar Cells Based on Low-Temperature Processed Electron Extraction Layer - Chan, Shun-Hsiang; Chang, Yin-Hsuan; Wu, Ming-Chung (Frontiers in Materials, 2019)
Organic-inorganic perovskite solar cells (PSCs) is considered as one of the most promising energy harvesting technology due to its high power conversion efficiency (PCE). T. Miyasaka group first reported the methylammonium lead halide (CH3NH3PbX3) as a light absorber of dye-sensitized solar cells with a PCE of 3.8% in 2009. Over the past decade, many research groups have been dedicated to construct high-performance PSCs and have obtained fantastic progress. Before commercialization, many issues have to be overcome. To extend the application of PSCs, flexible PSCs is seen as the preferred choice. However, the conventional process requires high-temperature procedures that are incompatible with the production of flexible PSCs. Here, we specifically focus on the recent developments of the low-temperature process strategies for fabricating high-performance PSCs. This mini-review briefly discusses the development in low-temperature processed metal oxide and carbon-based electron extraction layer (EEL). The approaches for low-temperature solution-processed PSCs are introduced and then the various PSCs with distinctive EEL are discussed. Overall, this mini-review contributes to a better understanding of the low-temperature processed electron extraction layer. Strategies and perspectives are also provided for further high-performance PSCs.